Special Issue on Programming Languages for Big Data Editorial. (12th March 2018) - Cheney, James; Grust, Torsten
Abstract : Ideas from programming languages play an important role in a range of advanced applications of databases, in database system implementation, distributed programming (MapReduce), streaming computation, and high-performance (GPU/multicore) computation. This creative research area is broadening into a subfield of data-centric computation. Although the interaction of databases and programming has a long history (the 16th biennial Database Programming Languages symposium was held in 2017), there has been a recent renewal of interest and broadening of programming language techniques for dealing with data from several quarters in the last few years, including workshops at Microsoft Research (RADICAL 2010), ICFP (XLDI 2012), POPL (DDFP 2013, DCM 2014) and a Dagstuhl Seminar on Programming Languages for Big Data (December 2014). This special issue recognises and encourages the publication of mature research contributions in this area.